Genetic improvement of the tolerance to high temperature and resistance to bean golden mosaic virus on common beans. - Rosas, Juan Carlos; Castro, Aracely; Beaver, James S.; Pérez, Carlos A.; Morales, Adrián; Lépiz, Rogelio (Agronomía Mesoamericana, 2006)
In 1994-95, sources of heat tolerance were identified in common beans after screened several germplasm and advanced lines nurseries in Choluteca and Nacaome (≤ 50 masl), in the southern region of Honduras. The best heat tolerant genotypes were validated under greenhouse controlled conditions (35/27 °C day/night) in Geneva, New York. Afterward, crosses were made to develop small-red bean lines with heat tolerance and resistance to BGMV and other limiting factors. The F2- F5 segregant populations were evaluated for multiple traits including BGMV, common bacterial blight, angular leaf spot, rust, low fertility conditions, and selected for agronomic performance and commercial value. In 1998, 217 F6 and F7 advanced lines were evaluated in the irrigation district Lempa-Acahuapa (20 masl), in the Pacific region of El Salvador for heat tolerance and BGMV. The same nurseries were evaluated in Liberia, in the Northwest region of Costa Rica, for tolerance to high temperatures; and at Zamorano, Honduras for resistance to common bacterial blight, angular leaf spot and rust. A group of lines were identified having superior yield and adaptation than commercial checks, under high temperature conditions in El Salvador and Costa Rica. Some of these lines were also resistant to BGMV in El Salvador, and moderate resistant to web blight in Costa Rica, and they had excellent agronomic performance and good commercial value.